1979
DOI: 10.1007/bf00344997
|View full text |Cite
|
Sign up to set email alerts
|

Net photosynthesis, root respiration, and regrowth of Bouteloua gracilis following simulated grazing

Abstract: Net photosynthesis (P), root respiration (R), and regrowth of Bouteloua gracilis (H.B.K.) Lag. were examined in the laboratory over a 10-day period following clipping to a 4-cm height to simulate grazing by large herbivores. Net photosynthesis rates of tissue remaining immediately following defoliation were only about 40% as great as preclipping rates. Three days after clipping, P rates of defoliated plants had increased to values about 21% greater (per unit leaf area) than those of unclipped controls and rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
91
0
3

Year Published

1980
1980
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(107 citation statements)
references
References 27 publications
11
91
0
3
Order By: Relevance
“…The CER T measurements were taken from 1000 to 1300 h (Mountain Standard Time) about every 3 wk during the growing seasons of 1995 through 1997. Measurements made on the treatment sites showed that maximum daily CER T occurred during 1000-to 1300-h period of the day, which agrees with Detling et al (1979). Each time CER T measurements were made, a point frame was used to determine the green vegetation index (GVI) within each of the CER frames (Warren-Wilson, 1963).…”
Section: Site Description and Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…The CER T measurements were taken from 1000 to 1300 h (Mountain Standard Time) about every 3 wk during the growing seasons of 1995 through 1997. Measurements made on the treatment sites showed that maximum daily CER T occurred during 1000-to 1300-h period of the day, which agrees with Detling et al (1979). Each time CER T measurements were made, a point frame was used to determine the green vegetation index (GVI) within each of the CER frames (Warren-Wilson, 1963).…”
Section: Site Description and Methodssupporting
confidence: 59%
“…Studies have shown that grazing affects SOC levels, either through changes in plant community (Coupland et al, 1960;Dormaar and Willms, 1990;Coupland, 1992) or by other more subtle and less discernable responses such as litter accumulation and decomposition rates, changes in chemical composition of soil organic matter (SOM), amount and quality of root exudates, increased root biomass, and more rapid cycling of C (Schuster, 1964;Smoliak et al, 1972;Dyer and Bokhari, 1976;Davidson, 1978;Christie, 1979;Detling et al, 1979;Holland and Detling, 1990;Naeth et al, 1991;Shariff et al, 1994;Ganjegunte et al, 2005). The quantity and chemical composition of SOM is important to C and N cycling, as N is often the limiting factor to productivity in rangeland ecosystems (Power, 1994).…”
Section: Ja Morganmentioning
confidence: 99%
“…Plants can also increase their net aboveground productivity when infested (Belsky, 1986 and references therein) and various mechanisms have been identified that could contribute to such compensatory growth. They include intrinsic mechanisms such as photosynthetic enhancement and reallocation of available assimilates (Delting et al, 1979;Oesterheld & McNaughton, 1988;Trumble et al, 1993) and extrinsic mechanisms such as nutrient recycling (Floate, 1981;Holland et al, 1992). Therefore, increased shoot growth could lead to increased root growth (McNaughton et al, 1998) and well nourished plants have a higher capability of compensating (and even overcompensating) than when nutrients are limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Les (Balent et Duru, 1984 Soulas, 1981). Ces modalités de coupe ont été choisies aussi d'après la bibliographie (McNaughton, 1979;Detling et al, 1979;Detling et al, 1980); -le facteur «thiamine» : la quantité de thiamine apportée est très faible : 0,2 ml d'une solution à 10 ppb (partie pour billion). Elle correspond à la quantité déposée par un animal selon Reardon et al (1974) et McNaughton (1985).…”
unclassified